Pengembangan Kecerdasan Buatan Objek NPC pada Micro-Games: Karting menggunakan Finite State Machine Unity - Muhammad Azzam Al-Ghifari Habiburrahman; Muhammad Aminul Akbar; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Video game development is a process of making a video game through many ways, and one of them is through game engine. Game engine is a tool to develop a video game without building its foundation first, because in many game engine, there is already many function that developer can easily understand and use. One of the most used and most popular game engine is Unity. Unity can provide a way to develop a video game through a template that fasten the development process. One of this template is Micro-Games Karting that can be downloaded directly at Asset Store Unity. This template already has many assets that developer can use, but there is still not available artificial intelligence to use for the non-playable character (NPC) model. To overcome the said problem, therefore the development of airtificial intelligence employing Finite State Machine decision making method is being developed. The artificial intelligence is a representation of the behavior of the drivers in racing in the real world. The artificial intelligence is tested with two type of tests, namely functional testing with the black box method and performance testing. The functional test results show that the artificial intelligence developed for NPCs using the Finite State Machines method has functionalities that are all valid in black box testing, and the performance test results shown by the NPCs when run have a good performance related to the ability to avoid collisions.